Study designs in medical research and their key characteristics - Nowak, Jan K.; Walkowiak, Jarosław (Journal of Medical Science, 2023)
Medical research study designs are many and varied. At first glance, they may be difficult to distinguish. Knowledge of their specific strengths and limitations is helpful for investigators planning new projects and for readers of the medical literature. The aims of the review are threefold: (i) to present an overview of medical research types, (ii) to attract attention to multiple characteristics of medical study designs, and (iii) to provide a concise educational resource for young researchers in the health sciences. Analysing the characteristics of medical study designs leads to achieving the goals.
Keywords: research methodology; study design; randomized controlled trial; cohort; case-control; review; cross-section